Diabetic Retinopathy Detection Using Convolution Neural Networks - Dileep Kumar Agarwal (International Journal of Intelligent Systems and Applications in Engineering, 2024)
An image is defined as a scalar in case of performing a single measurement at every location of the image. As the invasive devices, having higher speed, and more accuracy are developed rapidly, a great innovation can be seen in the progress of medical imaging in last few decades. There is a necessity of precise software for handling these kinds of images of higher quality. The previous technique aims to pre-process the image for detecting the diabetes retinopathy (DR) and deploys the textural feature analysis to extract the pre-processed image. The diabetic portion is segmented using an optical disk segmentation (ODS) method. This research work expands the previous technique with the implementation of Convolutional Neural Network (CNN) algorithm. Google Colab is executed to simulate the suggested technique. Various parameters are utilized to analyze the results.